University Network Capital as an Element of the City's Social Capital - R. A. Zayakina (Moscow Polytechnic University, 2021)
The formation and development of network capital in the university brings up the issue of its influence on characteristics of the city's social capital. The basic provisions of the network approach and the theory of social capital are used as theoretical grounds to identify such an impact. The article reveals the features of a modern university as a complex network object and the characteristics of interpersonal relationships that arise in its socio-cultural environment. These include the cultural homogeneity, formation of a joint reality, optimization of communication processes, the need for cooperation. Taking into account the revealed specificity, the network capital available to the subjects of social interaction is characterized and studied through the categories of trust and solidarity. It is determined that trust and solidarity are not only central, but necessary structural elements of the university's network capital, first of all, because the peculiarities of the organization of network interaction dictate the preferred strategies of network behavior, into which these phenomena are embedded. Thus, being the holder of intellectual resources and a network of interpersonal connections, the university produces the effective ways to expand the city's social capital, firstly, through a unique social network organization capable of rapid mobilization. It provides access to the formation of temporary teams with deep and versatile competencies that generate "quick trust". Secondly, it expands the city's social capital through impersonal trust, which convinces society that the university has some universal competence related to the life of the city and its people.